Identifikasi Risiko dan Penilaian Risiko terhadap Keterlambatan Proyek pada Pembangunan Apartemen Westown View Surabaya - Alfandi, Alfandi; Beatrix, Michella (Politeknik Negeri Lhokseumawe, 2023)
Risk management is a systematic method for managing risks that may occur so that they can be handled properly to avoid uncertainty in project activities. The risk that often occurs at the project stage during project implementation is the risk of project delays. This research aims to identify the risk of delays and determine the risk value for the ongoing project, namely the construction of the Westown View Apartments in Surabaya. The method used uses quantitative analysis with the help of a questionnaire with risk assessment using AS/NZS 4360: 2004 standards. The results of the research show that there are 21 risk variables in the construction of the Westown View Apartments in Surabaya, these variables include, (1) low labor productivity , (2) inexperienced workforce, (3) poor cooperation between workers, (4) unclear work instructions, (5) lack of materials, (6) late delivery of materials, (7) low quality materials, ( 8) limited number of work tools, (9) work tools have problems/damage, (10) tool operators lack expertise. Risk assessment using the AS/NZS 4360: 2004 standard contains 11 risk variables in the extreme risk category, 9 risk variables in the High risk category, and 1 risk variable in the medium risk category.